HUBUNGAN BAHAN ORGANIK TANAH DENGAN SUHU PERMUKAAN PADA BERBAGAI PENGGUNAAN LAHAN DI NAGARI PADANG LAWEH KABUPATEN SIJUNJUNG - Gunadi Gunadi; Juniarti Juniarti; Gusnidar Gusnidar (Fakultas Pertanian Universitas Muhammadiyah Tapanuli Selatan, 2020)
Padang laweh located in Koto VII, West Sumatra has 1.569,92 ha area which was dominated by mixed holder agriculture. The availability of soil organic C is influence by land management. Vegetation density will increase the soil organic C content, but an increase in soil temperature can increase the rate of soil organic matter decomposition which will decrease the soil organic C content. The purpose of study was to analyze the relation of soil organic matter (SOM) and soil organic carbon stock (SOCS) with land surface temperature. The study was conducted using a survey method consisting of 5 stage, namely preparation, pre survey, main survey, analysis of soil in laboratories and data processing. Soil sampling was taken in purposive random sampling under several land unit (LU), the LU were limited by soil order, slopes, and land use. Based on the land unit map, there are 14 land unit. Soil samples was taken in a composite manner at a depth of 0-20 cm. Parameter analysed were organic-C, particulate organic-C, and BD. Surface temperature measurement are carried out directly in the field using a mercury thermometer. The data of research result are processed statistically using simple linear regression equations. The result showed that the surface temperature measurement of rice field has highest temperature of 34 0C, and the rubber plantation has the lowest temperature 28 0C. Organic-C affects to soil BD, the higher organic-C value the lower BD value. The highest soil organic matter content (4.29%) and the highest carbon stock (41 kg/m2) was found in land unit 10 with rubber plantation with slope 8-15% and decreased with increasing slope. The results of the regression analysis showed that surface temperature did not have a significant effect on the value of SOM and SOCS.Keywords: Regresi equation, Soil survei, Topografi